Trends and Trajectories in Indonesian Multicultural Education (2000-2022): A Bibliometric Analysis Using Google Scholar and Vos Viewer - Utari, Tria Ina (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2023)
Purpose – The purpose of this study is to conduct a comprehensive bibliometric analysis of the evolution of multicultural education in Indonesia between 2000 and 2022. It aims to understand scientific article productivity, author contributions, thematic evolutions, keyword dynamics, and patterns of author collaboration in this domain. Design/methods– The study employs a bibliometric methodology, utilizing data indexed in Google Scholar and analyzed with Vos viewer software. The methods include examining scientific article productivity, author contributions, keyword co-occurrence, and patterns of author collaboration. Findings – The findings reveal Wekke as the leading author in this field, with the most prolific publication period being in 2013. C Mahfud's 2013 publication is identified as the most influential work with 1,475 citations. Key terms such as 'multicultural country', 'intercultural', 'diversity', and 'pesantren' were frequently observed, highlighting the multidimensionality of multicultural education in Indonesia. Research implications/limitations – The research acknowledges limitations, including potential oversights of non-indexed scholarly contributions and a lack of qualitative depth. It suggests future research directions focusing on qualitative aspects and expanding the scope of analysis to more academic databases. Practical implications – The study has significant implications for educational policy and curriculum development in Indonesia. It emphasizes the importance of diversity and inclusivity in educational settings and provides insights for policymakers and educators in adapting to the evolving educational needs of a diverse nation. Originality/value – This study is valuable as it provides a pivotal reference for the evolution of multicultural education in Indonesia, highlighting key authors, works, and thematic areas. Its originality lies in its comprehensive bibliometric approach and its focus on Indonesian multicultural education over two decades.